Meningkatkan Hasil Belajar Melalui Mind Mapping Mata Pelajaran IPA Kelas IV MIN 3 Medan - Annisyah Arifah (Program Studi PGSD Kampus UPI di Serang, 2021)
The use of Mind Mapping as an innovative learning model in learning is expected to foster high teacher-student interactions or between these students. This can make the learning climate in the classroom more active and more conducive. Students are able to show their competence to the maximum by carrying out various learning activities that are shown through various activities during the learning process. This type of research is Classroom Action Research (PTK), In accordance with the nature of classroom action research, this research was carried out with the stages of planning, action, observation, and reflection. with the conclusion of the first cycle meeting 1 of 28 students there was no significant increase, which was only 32%, but after being given the effectiveness category at meeting 2, there was an increase after that, namely 54%. Even so, it has not touched the classical KKM score of 75 and individual 70. From cycle II to meeting 1, there was a significant increase from 28 students, there were 71%, but furthermore there was an increase of 93% at meeting 2 and had reached classical 75 and individuals 70.